Environmental Product Declarations of Structural Wood: A Review of Impacts and Potential Pitfalls for Practice - Freja Nygaard Rasmussen; Camilla Ernst Andersen; Alexandra Wittchen; Rasmus Nøddegaard Hansen; Harpa Birgisdóttir (Buildings, 2021)
The use of wood and timber products in the construction of buildings is repeatedly pointed towards as a mean for lowering the environmental footprint. With several countries preparing regulation for life cycle assessment of buildings, practitioners from industry will presumably look to the pool of data on wood products found in environmental product declarations (EPDs). However, the EPDs may vary broadly in terms of reporting and results. This study provides a comprehensive review of 81 third-party verified EN 15804 EPDs of cross laminated timber (CLT), glulam, laminated veneer lumber (LVL) and timber. The 81 EPDs represent 86 different products and 152 different product scenarios. The EPDs mainly represent European production, but also North America and Australia/New Zealand productions are represented. Reported global warming potential (GWP) from the EPDs vary within each of the investigated product categories, due to density of the products and the end-of-life scenarios applied. Median results per kg of product, excluding the biogenic CO2, are found at 0.26, 0.24, and 0.17 kg CO2e for CLT, glulam, and timber, respectively. Results further showed that the correlation between GWP and other impact categories is limited. Analysis of the inherent data uncertainty showed to add up to ±41% to reported impacts when assessed with an uncertainty method from the literature. However, in some of the average EPDs, even larger uncertainties of up to 90% for GWP are reported. Life cycle assessment practitioners can use the median values from this study as generic data in their assessments of buildings. To make the EPDs easier to use for practitioners, a more detailed coordination between EPD programs and their product category rules is recommended, as well as digitalization of EPD data.